Extension of the Deep UV‐Capabilities in Multiwavelength Spectrometry in Analytical Ultracentrifugation: The Role of Oil Deposits. (18th February 2016) - Walter, Johannes; Segets, Doris; Peukert, Wolfgang
Abstract : The optical performance of an analytical ultracentrifuge equipped with a fiber‐coupled detector is investigated with special emphasis on the influence of oil leakage on the long‐term deep ultraviolet stability. Two strategies for enhanced optical performance are presented. The first includes regeneration of fiber transmittance under atmospheric conditions, whereas the second utilizes an optimized vacuum system consisting of a turbomolecular pump.